The Goalkeeper The Nabokov Almanac - Leving, Yuri (Academic Studies Press, 2010)
"The Goalkeeperis a new scholarly almanac devoted to the art of Vladimir Nabokov.Himself an ardent goalkeeper, the author of Lolita viewed soccer as more thana game: "I was less the keeper of a soccer goal than the keeper of a secret" (Speak,Memory). The inaugural collection features contributions from two dozen leading Nabokov scholars worldwide, including academic articles (Neil Cornwell, Gerard de Vries, Samuel Schuman, and others); roundtable discussions (Brian Boyd, Jeff Edmunds, Priscilla Meyer, David Rampton, Leona Toker); interviews (Dmitri Nabokov,Alvin Toffler); archival materials; the Kyoto Nabokov conference report; and book reviews (Pekka Tammi, Zoran Kuzmanovich, Galya Diment). The Nabokov Almanac, edited by Yuri Leving, is affiliated with the Nabokov Online Journal, published since 2007."